Adverse childhood experiences and suicidal ideation among nurses in China - Ying Ling; Xijie Hou; Jie Zhang; Jie Zhang (Frontiers in Psychiatry)
Background and AimsSuicidal ideation and behaviors constitute a serious public health issue both globally and in China, with nurses having a relatively higher suicide rate. While existing research has established that adverse childhood experiences (ACEs) may increase the risk of suicide-related behaviors, the precise mechanisms by which ACEs influence suicidal ideation remain underexplored, particularly among nurses. This research investigates the association between ACEs and suicidal ideation, while also analyzing the mediating effect of psychological strain and the moderating influence of impulsivity.MethodsTwo top public hospitals, one in Southern China and the other Eastern China, were selected to recruit young nurses for study. The sample consisted of 395 individuals with 80.76% being female and aged between 19 and 42 years. A self-reporting questionnaire survey was administered with a computerized program.FindingsPsychological strain partially mediates the association between ACEs and suicide ideation, with the mediator effect representing 21.70% of the total effect. Impulsivity served as a moderator in the connection between ACEs and suicidal ideation.ConclusionThis study discloses how ACEs can directly and indirectly influence nurses’ suicidal ideation through psychological strain, and how impulsivity moderates the connection between ACEs and suicidal ideation. The research findings offer significant practical evidence for enhancing nurses’ mental health levels. Future studies could focus on improving nurses’ mental health by addressing factors like mitigating the impact of ACEs, reducing psychological strain, and managing impulsivity.